Sports-based distribution of facial fractures - findings from a four-season country - Puolakkainen Tero; Murros Olli-Jussi; Abio Anne; Thoren Hanna; Snäll Johanna (TAYLOR & FRANCIS LTD, 2022)
Objective: The aim of this study was to elucidate the relationship between injury mechanisms and sports-related facial fractures, and to evaluate the changes in incidence rates of facial fractures sustained in sports-related events in a 30-year period.
Material and methods: This retrospective cohort study included all patients sports-related facial fractures admitted to a tertiary trauma centre during 2013-2018. Specific fracture types, sports, injury mechanisms as well as patient- and injury related variables are presented. The results underwent evaluated statistically with logistic regression analysis.
Results: Facial fractures occurred most frequently while playing ice hockey and football. Unilateral zygomatic-maxillary-orbital and isolated mandibular fractures accounted for 74.2% of all fracture types. In total, 99 patients (46.5%) required surgical intervention for their facial injuries. About 12.7% of patients sustained associated injuries in addition to facial fractures. Overall, the number of sports-related facial fractures has increased during the last three decades mostly due to the surging rates of ice hockey- and football-related facial fractures.
Conclusions: Sport-related facial fractures have markedly increased in different sports disciplines during the past decades. The use of safety gear to protect the facial area should be enforced particularly in ice hockey.